The Effect of Environmental Factor, Population and Age of Duck on Egg Production - Ismoyowati Ismoyowati; Imam Suswoyo; Rosidi Rosidi; Sigit Mugiyono; Nu'man Hidayat (ANIMAL PRODUCTION, 2020)
Duck is one of the commodities that contribute to the national livestock production and Central Java is home to the fourth biggest duck population after West Java, South Sulawesi and East Java. The 2019 egg production in Central Java was 36.174 tons or 11.3% of the total egg production nationwide. Accordingly, it is important to investigate the effect of environmental factor, total number and age of ducks on egg production in Central Java. Specifically, this study aimed to observe the effect of region on egg production and feed conversion ratio (FCR) and the total livestock (chicken), age (month), stocking density (ducks/m2), internal housing temperature (oC), and humidity (%) on Hen day production/HDP. A survey engaging purposive random sampling was conducted on the population of duck farming in Central Java especially Tegal, Pemalang and Brebes districts. The data were subjected to General Linear Model (GLM) and a regression-correlation analysis using an SPSS program. The result showed that region significantly affected hen day production (HDP) but did not affect FCR. Housing temperature affected HDP by 14.9% and the higher the temperature, the lower the HDP. Duck age affected HDP by 11.7%, and the older the ducks the lower the egg production. Duck population, stocking density and humidity did not significantly affect egg production. Conclusively, duck egg production (HDP) is significantly affected by temperature inside the housing and the duck age.